2020
DOI: 10.3390/md18090441
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Route for the Synthesis of Tetracyclic Meroterpenoids: (±)-Aureol Preparation and Mechanistic Interpretation

Abstract: A new concise general methodology for the synthesis of different tetracyclic meroterpenoids is reported: (±)‑aureol (1), the key intermediate of this general route. The synthesis of (±)‑aureol (1) was achieved in seven steps (28% overall yield) from (±)‑albicanol. The key steps of this route include a C–C bond-forming reaction between (±)‑albicanal and a lithiated arene unit and a rearrangement involving 1,2‑hydride and 1,2-methyl shifts promoted by BF3•Et2O as activator and water as initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…With alkyl iodide 52 in their hands, the cross-coupling reaction between Grignard reagent 53 and alkyl iodide 52 generated the key intermediate 51 in a 56% yield. As olefin 51 was an advanced intermediate in the Rosales’s synthesis [ 38 , 39 ] of (±)-aureol ( 1 ), their strategy constituted a formal synthesis of (+)-aureol ( 1 ). This formal synthesis was completed in four steps (27% overall yield) from starting material (+)-sclareolide ( 47 ).…”
Section: Synthesis Of Aureolmentioning
confidence: 99%
See 3 more Smart Citations
“…With alkyl iodide 52 in their hands, the cross-coupling reaction between Grignard reagent 53 and alkyl iodide 52 generated the key intermediate 51 in a 56% yield. As olefin 51 was an advanced intermediate in the Rosales’s synthesis [ 38 , 39 ] of (±)-aureol ( 1 ), their strategy constituted a formal synthesis of (+)-aureol ( 1 ). This formal synthesis was completed in four steps (27% overall yield) from starting material (+)-sclareolide ( 47 ).…”
Section: Synthesis Of Aureolmentioning
confidence: 99%
“…As a part of our efforts directed towards the synthesis of marine terpenoids [ 40 ], we embarked on a project aimed at the divergent synthesis of tetracyclic meroterpenoids. Our endeavors started with the racemic preparation of (±)-aureol ( 1 ) in 2015 [ 38 ], a process we latter improved in 2020 [ 39 ]. This effort continues with the divergent synthesis of other tetracyclic meroterpenoids using aureol ( 1 ) as a common synthetic intermediate.…”
Section: Synthesis Of Aureolmentioning
confidence: 99%
See 2 more Smart Citations
“…Martinez et al showed a concise strategy for the preparation of sponge derived tetracyclic meroterpenoids characterized by a sesquiterpene skeleton linked to a phenolic or quinone part [8]. Aureol, strongylin A, cyclosmenospongine and smenoqualone are representative examples of this class of bioactive compounds.…”
mentioning
confidence: 99%